SPEESH: Speech-based mobile application for dysarthric speech recognition - Mohamad Nasir A.B.; Nasir N.R.M.; Salleh F.H.M. (IOP Publishing Ltd, 2023)
Character recognition; Speech; User experience; Automatic speech recognition; Communication platforms; Mobile applications; Speaker model; Speech disabilities; Speech disorders; Speech recognition systems; Text independents; Speech recognition